Healthy Environments, Healing Spaces : Practices and Directions in Health, Planning, and Design - Rainey, Reuben M.; Jones, Carla; Beatley, Timothy, 1957- (Book collections on Project MUSE., 2018)
This collection of essays by leading scholars and practitioners addresses a timely and essential question: How can we design, plan, and sustain built environments that will foster health and healing? With a salutogenic (health-promoting) focus, 'Healthy Environments, Healing Spaces' addresses a range of contemporary issues, including health equity, biophilic cities, healthcare facility design, environmental health, aging in place, and food systems planning.